Numerical Investigations on the Port Flow Field of a Two-Stroke Poppet Valve Engine - Mohd Razali, Hanipah; Zamri, Mohamed (2016)
This paper describes the model and simulation results of port flow field investigations on a two-stroke poppet valve engine. Higher power to weight ratio has been the advantage of a two-stroke engine over the four-stroke engine. However, poor emissions have plagued two-stroke ported design which is the main design mass produced for small engines. By employing poppet valve configuration, the gas exchange performance, hence the emissions can be improved. In order to verify this, two-dimensional (2D) and three-dimensional models of the two-stroke poppet valve engine are developed to illustrate the port flow field with the proposed valve timings obtained from the one-dimensional numerical analysis. Several design changes on the cylinder are proposed and investigated through the simulation. Further insight into the fluid mechanics of the flow into the engine can be provided by examining the in-cylinder velocity flow fields. The 2D simulation results have shown that by having a shroud on the inlet valve, the short-circuiting can be minimised without any modification on the cylinder head. Further, the 3D simulation results have shown sufficient swirl occurs in the cylinder but the tumble flow is not apparent.